2017
DOI: 10.1080/10942912.2017.1362652
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and melting properties of sucrose-free dark chocolate

Abstract: In this study, sugar-free dark chocolate was produced from isomalt and maltitol by β V seeding technique as an alternative to conventional tempering process. The effect of β V seed concentrations on the particle size distribution (PSD), textural, rheological and melting properties of the final products were examined and the results were compared with those of conventional sugar-free dark chocolates. For this aim, conched dark chocolates were melted and crystallised with β V seeds which were added at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As previous studies have shown, the rheological properties of chocolate are affected by the incorporation of other products and, particle size is inversely correlated with the firmness, consistency, cohesiveness, viscosity and hardness of chocolate bars (67,73). Smaller particles have also been found to favor higher dispersibility of chocolate ingredients, because they occupy the spaces between larger particles, leading to a lubricating effect with a consequent reduction in viscosity (68).…”
Section: Rheological Propertiesmentioning
confidence: 92%
“…As previous studies have shown, the rheological properties of chocolate are affected by the incorporation of other products and, particle size is inversely correlated with the firmness, consistency, cohesiveness, viscosity and hardness of chocolate bars (67,73). Smaller particles have also been found to favor higher dispersibility of chocolate ingredients, because they occupy the spaces between larger particles, leading to a lubricating effect with a consequent reduction in viscosity (68).…”
Section: Rheological Propertiesmentioning
confidence: 92%
“…The addition of the sugar particles promoted the formation of polymorphs with lower melting points. It was suggested that the sugar acted as a heterogeneous nucleation agent, prolonging the nucleation and growth of cocoa butter crystals since foreign surfaces acted as nucleation sites for crystallisation (Konar et al ., 2017; Oba et al ., 2017). Optimization of the tempering heat program and process conditions may be required in chocolate production using polyol (Toker et al ., 2020).…”
Section: Selection Of Appropriate Polyols For Use In Chocolatementioning
confidence: 99%
“…Polyols, such as maltitol, affect seeding technique (β V stable cocoa butter crystal) and rheological, textural, and thermal characteristics of dark chocolates [19]. Temper index value (TIV) gives information about tempering degree of the chocolates.…”
Section: The Basic Important Physical and Chemical Parameters Of Diffmentioning
confidence: 99%
“…Thermal characteristics, such as melting, were determined by DSC method (differential scanning calorimeter). The sweetener concentration, as well as seeding, didn't change melting characteristics at all [19]. Rheological properties are described by the flow curves where the shear stress of the sugar-free chocolates is a function of shear rate.…”
Section: The Basic Important Physical and Chemical Parameters Of Diffmentioning
confidence: 99%
See 1 more Smart Citation